Analisis Sifat Mekanis Komposit Barium Hexaferrit dengan Penguat Silika - Ari Wibowo (JURNAL INTEGRASI, 2015)
barium heksaferit widely used as a magnetic material. The higher mechanical strength of the material, it will result the better application. This experiment aims to determine the effect of adding silica composition and sintering temperature on barium hexaferrit matrix composites against mechanical properties. Barium hexaferrit material was ball milled so that the size of the powder can be ≤ 74μm. The obtained Barium hexaferrite powder is then mixed with a silica composition of 0%, 1%, 2%, 3%, 4%. The mixture was then pressed with pressure 23 Mpa to shape the hardness, bending and impact test specimens. The green body was then sintered at 1000oC, 1100oC and 1200oC temperature for 3 hours with air environment. Composites already made and then tested with density test, bending test, impact test and microstructure test. Best mechanical properties obtained on the composition of SiO2 1 wt.% And the sintering temperature 1100oC.